FINANCIAL RISK MANAGEMENT IN THE INSURANCE INDUSTRY - Cummins, J. David; Phillips, Richard D.; Smith, Stephen D. (Assurances)

(untitled) (HEC Montréal, 2000)
This paper has two objectives. The first objective is to survey the finance literature on corporate hedging and financial risk management with an emphasis on how the general literature applies in insurance. We begin by reviewing the theoretical rationales for widely-held, risk-neutral, profit-maximizing firms to practice risk management and then go on to discuss the empirical literature on corporate hedging. The second objective is to develop a theoretical model to provide a new explain of why widely-held insurers manage risk. Insurers are hypothesized to invest in multiple period, private assets where the payoffs are not fully realized if the assets have to be liquidated prior to their expiration. A voiding adverse shocks to capital that would trigger a liquidation provides the motivation for risk management in our model.